Ethics and Ageing in the 21st Century - McNamara, Laurence J. (Journal of religious gerontology, 2002)
This article insists that a cautious view of population data about ageing is necessary. Against this background three questions of meaning are explored, namely, what does it mean to grow old? What does it mean to be healthy or ill when one is old? What does it mean to care for aged persons in an age of chronic illness and disability? These questions raise justice issues about distribution of resources and quality of life and bring into focus theological insights about the human person, human solidarity and human virtues in a way that contributes to public discourse about ethics and ageing.